Evaluation of Anatomical and Biochemical Causes for Seed Deterioration in Rice Genotypes under Ageing - K RAJA; R JERLIN; J RUNUGADEVI; C TAMILARASAN; K PARAMESWARI (Seed Research, 2026)
Seed deterioration is an undesirable event occurs with ageing that decreases the ability of the seed to survive. Deterioration is generally fast in oil and pulses seeds than cereals. Rice is an important cereal food crop and consumed by more than 60 per cent of the people in the world. Though loss in viability of rice under ageing is not the major concern, some of the important rice genotypes lose their viability very quickly. In Tamilnadu, ADT 38, and ADT (R) 46 are important medium duration rice genotypes in seed supply chain and both the varieties loses their germinability very quickly as the storage time advances. In order to conserve the ADT (R) 46 seeds from loss, the causes for poor storability was studied under accelerated ageing in comparison with ADT 39, ADT (R) 49 and ADT (R) 50 genotypes. The results revealed that variety ADT (R) 46 lost its viability quickly as compared to other varieties. The histological study revealed that all the genotypes except ADT (R) 46 had undamaged aleurone layer with intact cell and distinct cytoplasm even after 10 days of accelerated ageing whereas, variety ADT (R) 46 had collapsed aleurone layer with poor distinct cytoplasm of cells which causes poor germination during ageing.